2013
DOI: 10.1155/2013/969405
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Tibial Tubercle Sleeve Fractures in a Skeletally Immature Patient

Abstract: Tibial tubercle sleeve fracture is a rare injury. In concept, it is similar to the patellar sleeve fracture in a skeletally immature patient. We describe a unique case of simultaneous bilateral tibial tubercle sleeve fractures in a 12-year-old boy. Radiographs and MRI confirmed the injury. The patient underwent open surgical repair of bilateral sleeve fractures with suture anchor fixation. At the final followup, 3 years after his initial injury, the patient demonstrated full knee function bilaterally without r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…Rupture in these individuals however remains low. Unlike the other case of tibial tuberosity avulsion fractures ( 1 , 3 , 6 ) in this case the MRI scan confirmed severe patellar tendinosis affecting the whole of the patellar tendon. Repetitive microtrauma may well have been a predisposing factor in this case.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Rupture in these individuals however remains low. Unlike the other case of tibial tuberosity avulsion fractures ( 1 , 3 , 6 ) in this case the MRI scan confirmed severe patellar tendinosis affecting the whole of the patellar tendon. Repetitive microtrauma may well have been a predisposing factor in this case.…”
Section: Discussioncontrasting
confidence: 43%
“…A high level of clinical suspicion is essential to detect this injury. Bilateral ruptures of the extensor mechanism in preadolescence is extremely rare ( 7 - 9 ) and there is only one report of this occurring as a sleeve fracture in the literature ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The quadriceps undergoes an eccentric load avulsing the patellar tendon complex. Failure of the patellar tendon is relatively uncommon among extensor mechanism injuries of the knee [ 1 , 5 ]. Zernicke et al [ 6 ] reported that a load of 17.5 times the body weight is required to rupture the human patellar tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the distinguishing between patella tendon rupture and avulsion fracture was difficult in the present case because the fleck of bone was tiny and the displacement was minimal. Desai and Parikh [ 5 ] reported that a high-riding patella, palpable gap at the site of the patellar tendon, and an inability to perform active extension are important findings suggestive of patellar tendon injuries. Although physical examination is important, such examination is difficult to perform because of the swelling and pain around the knee in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%